Clinical Forensic Assessment of Victim with Sharp Force Injury (A Case Report) - Putri, Jeanaya Hedya Alfara; Hamdy, Irza Hasanal; Haris, Ivana Angelica; Nahdah, Jaudah; Putri, Jenniefer Clarissa (UNUSA Press, 2022)
Background: Violence or trauma committed against living victims can take many different forms, including blunt force, sharp force, or other types of injury. Because sharp weapons are simple to get, violent criminal acts frequently involve them. Homicide, suicide, and accidents can all result in deaths from sharp items. Objective: This study aims to dtermine the diagnosis wound qualification on the examination on patient in the emergency room of the Bhayangkara H.S. Samsoeri Mertojoso Hospital. Methods: The method of diagnosis uses a clinical assessment and based on Criminal Code’s Criteria. Result: A 61-year-old male victim with the initials JA who claimed to have experienced sharp force injury was reported. Upon inspection of the victim, an open wound of approximately 3 cm in length, 1 cm in width, and approximately 2 cm in depth was discovered on the outside left upper arm. The patient got wound hecting and medicine to reduce the pain. After that the patient release from hospital. Conclusion: Wounds on the patient's body are criminally caused injuries that fall under the category of minor abuse, meaning they don't make the victim sick or make it difficult for them to accomplish their jobs.